A zinc ferrochromate (ZnCr 2-x Fe x O4) spinel electrocatalyst and its preparation method and application
By introducing Cr and Fe into zinc-based spinel, a dual-active site system was constructed, and ZnCr2-xFexO4 electrocatalyst was prepared, which solved the problem of low activity and selectivity of the existing catalysts, and achieved the effect of efficient electrochemical synthesis of ammonia at room temperature and pressure.
Patent Information
- Application Number
- CN202211297093.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-10-21
AI Technical Summary
The existing electrocatalytic nitrogen reduction synthesis ammonia catalysts are limited by the linear relationship of adsorption energy, and their catalytic activity and selectivity are low. In particular, the front transition metal elements are prone to form stable nitride phases to hinder the hydrogenation step, while the latter transition metals are not selective due to excessive hydrogen adsorption.
By introducing zinc ferrochromate spinel electrocatalyst, using a dual active site system of Cr and Fe, synergistically to avoid linear relationship limitations, ZnCr2-xFexO4 (x=0,0.4,0.8,1.2,1.6,2) electrocatalyst was prepared. The method includes mixing zincate, chromate and ferrite in a certain proportion, adjusting the pH value, carrying out hydrothermal reaction and calcining, and obtaining nano zinc ferrochromate spinel electrocatalyst.
It has achieved efficient electrochemical synthesis of ammonia at room temperature and pressure, with ammonia production rate and Faraday efficiency reaching 29.26μg h-1cm-2 and 18.41%. At the same time, the catalyst preparation raw materials are easy to obtain, low cost, simple operation, good controllability, and suitable for mass production.
Smart Images

Figure BDA0003903198740000071 
Figure HDA0003903198750000011 
Figure HDA0003903198750000012
Abstract
Description
Technical Field
[0001] The present invention relates to a zinc ferrochromate (ZnCr 2-x Fe x O4) spinel electrocatalyst preparation method and its application in electrochemical synthesis of ammonia. Background Art
[0002] Ammonia is one of the chemical substances produced in large quantities in the world, with an annual output of more than 182 million tons, mainly used as synthetic fertilizer. Ammonia also has the advantages of high hydrogen content (mass ratio of 17.6%), high energy density, and easy liquefaction, and is expected to become a clean hydrogen storage carrier. At present, ammonia is synthesized from nitrogen and hydrogen under high temperature and high pressure (300-500℃, 200-300atm) by catalytic Haber-Bosch process, which requires large factories and high investment, and energy consumption accounts for about 1-2% of the world's total energy consumption. At the same time, it emits 1.5% of the world's carbon dioxide each year. Therefore, it is a dream to achieve efficient synthesis of ammonia at room temperature and pressure. Electrochemical synthesis of ammonia uses water as hydrogen source, can be carried out at room temperature and pressure, and can be driven by electricity converted from green energy such as solar energy or wind energy. It will be able to completely overcome the problems faced by the Haber-Bosch method of synthesizing ammonia involving energy consumption, pollution and safety, and is considered to be a potential alternative technology for synthesizing ammonia. However, to date, the core electrocatalytic nitrogen reduction ammonia synthesis catalysts are severely limited by the linear relationship of adsorption energy, and the catalytic activity and selectivity are still at a low level. Early transition metal elements (elements on the left of the periodic table) such as chromium (Cr), vanadium (V) and manganese (Mn) with strong N2 adsorption are easy to form stable nitride phases in the ammonia synthesis reaction atmosphere, which hinders the subsequent hydrogenation step and has poor ammonia synthesis activity; while late transition metals (elements on the right of the periodic table) such as ruthenium (Ru) and iron (Fe) with relatively weak N2 adsorption have relatively moderate N2 adsorption energy and show excellent electrocatalytic ammonia synthesis activity, but have strong hydrogen adsorption and cannot effectively inhibit the hydrogen evolution reaction (HER), and the selectivity is not ideal. How to break through this restrictive relationship has become the kinetic bottleneck of the current development of electrochemical ammonia synthesis. Therefore, developing catalyst materials that can break the limitations of linear relationships is a major problem facing scientists.
[0003] Spinel (with the general structural formula of AB2O4) has a cubic crystal structure, oxygen ions are closely packed in a cubic pattern, divalent cations A occupy tetrahedral voids with four times coordination, and trivalent cations B occupy octahedral voids with six times coordination. The types of cations at the A and B positions of spinel materials can be controlled, and the distribution of cations has a significant impact on the properties of spinel materials. It has been widely used in magnetic materials, microwave dielectric materials, humidity and gas sensitive materials, and chemical catalysis. Literature (Journal of Hebei University (Natural Science Edition), 2012, 12 (6): 619-622) uses a solid phase method to prepare ZnCr2O3 from ZnO, Fe2O3, and Cr2O3 as raw materials by grinding and high temperature calcination. 2-x Fe x O4 (x = 0, 0.3, 0.5, 0.8, 1.0) series spinels are used as magnetic materials. It is found that a high temperature of more than 1100 ° C is required to successfully dope Fe at the B position. 3+ , and the prepared material is not of high purity and contains impurities such as Cr2O3 and ZnO, which affects its further application. The literature (Results in Physics, 2021, 28:104622) uses zinc nitrate, nickel nitrate, chromium nitrate and iron nitrate powder as raw materials and uses microwave combustion method to prepare Ni with Zn partially replaced by Ni and Cr at the A position as glycine fuel. 0.4 Zn 0.6-x Cr x Fe2O4 (0.0≤x≤0.6) series spinels are used as magnetic materials. 3+ Pure ZnCr 2-x Fe x The O4 synthesis method is of great significance. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the present invention provides a method for preparing zinc chromite spinel electrocatalyst and its application, wherein the early transition metal Cr and the late transition metal Fe are introduced into the octahedral voids of the zinc-based spinel to form a double active site system, and a zinc chromite ZnCr is prepared. 2-x Fe x O4 (x = 0, 0.4, 0.8, 1.2, 1.6, 2) electrocatalysts, through the synergistic effect of Cr and Fe active sites, circumvent the linear relationship limitations of a single transition metal to a certain extent and achieve efficient electrocatalytic synthesis of ammonia.
[0005] The technical solution of the present invention is: a method for preparing zinc chromite spinel electrocatalyst, the specific steps are:
[0006] In the first step, zincate, chromate and ferrite are weighed in a certain proportion and dissolved in a solvent, and then an alkali solution is added to adjust the pH to 10-12, followed by a hydrothermal reaction, and a dry catalyst precursor is obtained after post-treatment.
[0007] The molar ratio of zincate, chromate and ferrite is 1:(2-x):x, where x is greater than 0 and less than 2;
[0008] The hydrothermal synthesis temperature ranges from 150°C to 200°C;
[0009] In the second step, the catalyst precursor obtained after drying in the first step is calcined in a muffle furnace, and then naturally cooled to room temperature and ground to obtain the desired electrocatalyst;
[0010] Furthermore, in the above technical solution, in the first step, the solvent is deionized water; and the alkaline solution is a 3.0-6.0 mol / L sodium hydroxide or potassium hydroxide aqueous solution.
[0011] Furthermore, in the above technical scheme, in the first step, the hydrothermal reaction and post-treatment are to transfer the metal precursor into a hydrothermal reactor with a polytetrafluoroethylene lining for hydrothermal reaction at a certain temperature for a certain time. After the reaction, the supernatant is removed by centrifugation to obtain a catalyst precursor, which is washed three times with deionized water and vacuum dried.
[0012] Furthermore, in the above technical solution, in the first step, the hydrothermal synthesis time ranges from 4 hours to 12 hours, and the vacuum drying temperature ranges from 60°C to 80°C.
[0013] Furthermore, in the above technical solution, in the first step, the zincate includes zinc chloride, zinc sulfate, zinc nitrate and zinc acetate; the chromate includes chromium chloride, chromium sulfate and chromium nitrate; the ferrite includes ferric chloride, ferric sulfate and ferric nitrate; and the concentration of the zincate is 0.05-0.2 mol / L.
[0014] Furthermore, in the above technical solution, in the second step, the calcination temperature ranges from 300° C. to 500° C., and the calcination time ranges from 0.5 hour to 3 hours.
[0015] Furthermore, in the above technical scheme, in the first step, the zincate, chromate and ferrite are zinc acetate, chromium chloride and ferric chloride respectively, the molar ratio of the three is 1:1.2:0.8, the concentration of zinc acetate is 0.1 mol / L, the hydrothermal synthesis temperature is 180°C, and the hydrothermal synthesis time is 8 hours; in the second step, the roasting temperature is 400°C, and the roasting time is 1 hour.
[0016] The present invention provides a pure zinc chromite spinel electrocatalyst obtained by the above method, which has the general formula ZnCr 2-x Fe xO4 represents, 2-x, x represents the atomic ratio of each element, and x is greater than 0 and less than 2.
[0017] Furthermore, in the above technical solution, x is selected from any number among 0.4, 0.8, 1.2, and 1.6.
[0018] The present invention provides an application of the electrocatalyst prepared by the above method in electrochemical synthesis of ammonia. The specific process is: the prepared electrocatalyst is loaded onto a carbon felt as a cathode, the carbon felt without the catalyst loaded is used as an anode, a KOH aqueous solution is used as an electrolyte, high-purity nitrogen is blown to the cathode at a certain flow rate (200 ml / min), and then a DC power supply is connected to perform electrolysis at a constant voltage (1.5 to 2.5 V) at room temperature and pressure, and the electrocatalyst has excellent electrochemical reduction of nitrogen to produce ammonia performance.
[0019] The present invention has the following beneficial effects: (1) The raw materials required for the preparation of the catalyst are easily available, the cost is low, the operation is simple, the controllability is good, and it is easy to mass produce. (2) The catalyst for electrochemical synthesis of ammonia prepared by the present invention is nano zinc chromite spinel. (3) Using the prepared electrocatalyst, with 0.1 mol / L KOH aqueous solution as electrolyte and nitrogen as raw gas, the ammonia production rate and Faraday efficiency of electrochemical synthesis of ammonia can reach up to 29.26 μg h -1 cm -2 The term "Faraday efficiency" refers to the percentage of actual ammonia generated to the theoretical electrochemical ammonia generated. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the XRD pattern of the catalyst prepared in Example 1;
[0021] Figure 2 The ZnCr2O4 and ZnCr 1.2 Fe 0.8 XPS characterization results of O4 and ZnFe2O4 catalysts;
[0022] Figure 3 The ZnCr prepared in Example 1 1.2 Fe 0.8 TEM and HRTEM characterization results of O4 catalyst;
[0023] Figure 4 The ZnCr2O4 and ZnCr 1.2 Fe 0.8 The results of nitrogen temperature-programmed desorption of O4 and ZnFe2O4 catalysts;
[0024] Figure 5 The electrochemical ammonia synthesis performance of the catalyst prepared in Example 1 at 2.1V;
[0025] Figure 6 ZnCr prepared in Example 1 1.2 Fe 0.8 Current density of ammonia synthesis by O4 catalyst at different electrolysis voltages;
[0026] Figure 7 ZnCr prepared in Example 1 1.2 Fe 0.8 Ammonia production rate and Faraday efficiency of O4 catalyst for ammonia synthesis at different electrolysis voltages;
[0027] Figure 8 XRD pattern of the sample prepared in Comparative Example 1;
[0028] Fig. 9 XRD pattern of the sample prepared in Comparative Example 2. DETAILED DESCRIPTION
[0029] The above content of the present invention is further described in detail below through embodiments.
[0030] Example 1
[0031] (1) According to the chemical formula ZnCr 2-x Fe x O4 (x = 0, 0.4, 0.8, 1.2, 1.6, 2) gives the ratio 1: (2-x): x. Weigh 5 mmol of zinc acetate and the corresponding amounts of chromium chloride and ferric chloride and dissolve them in deionized water to obtain 6 solutions with different ratios. Use 3.0 mol / L sodium hydroxide aqueous solution to adjust the pH of the solution to 10-12, and then add water to make the total volume of the solution 50 ml. Then transfer them into 6 hydrothermal reactors with polytetrafluoroethylene linings for hydrothermal reaction at 180°C for 8 hours. After the reaction, centrifuge to remove the supernatant to obtain 6 catalyst precursors, wash them 3 times with deionized water, and vacuum dry them for use.
[0032] (2) The catalyst precursors obtained after drying were calcined in a muffle furnace at 400° C. for 1 hour, cooled naturally to room temperature, and then ground to obtain the desired electrocatalyst.
[0033] The catalyst obtained in Example 1 was subjected to X-ray diffraction (XRD) analysis. Figure 1It can be seen that all samples have similar XRD spectra, with obvious characteristic diffraction peaks near 2θ=18.4°, 30.3°, 35.7°, 43.4°, 53.9°, 57.4° and 63.1°, which are attributed to the (111), (220), (311), (400), (422), (511) and (440) crystal planes of ZnCr2O4 spinel standard card PDF no.22–1107 and ZnFe2O4 spinel standard card PDF no.22–1012. At the same time, no other impurity peaks appear, indicating that the prepared catalyst has a spinel structure and no impurity phase. With the increase of Fe content (x value), all characteristic diffraction peaks move toward the direction of small 2θ angles. For the diffraction peak corresponding to the (311) crystal plane appearing in the XRD spectrum, according to the crystal plane spacing formula 1 / d 2 hkl =(h 2 +k 2 +l 2 ) / a 2 and Bragg equation nλ=2d hkl sinθ (where a is the lattice constant, h, k and l are the crystal plane Miller indices, d hkl is the interplanar spacing of (h, k, l) crystal planes, n is the diffraction order, usually n = 1, λ is the X-ray wavelength, Cu Kα1 (λ = 0.15406nm), θ is the diffraction angle) to calculate the (311) interplanar spacing of catalysts with different compositions. The calculation shows that when the x value increases from 0 to 2, the lattice constant a increases from Gradually increase to This indicates that the increase in Fe content leads to lattice expansion, which is mainly due to the larger radius of Fe 3+ ion The smaller radius replaces the center of the spinel octahedron. This also indicates that the Cr at the octahedral center 3+ Partly Fe 3+ Replace and together form a uniform, single-phase spinel crystal.
[0034] The ZnCr2O4 and ZnCr 1.2 Fe 0.8 The O4 and ZnFe2O4 catalysts were characterized by X-ray photoelectron spectroscopy (XPS). Figure 2 The Zn 2p spectrum in a shows two peaks at binding energies of 1021.4eV and 1044.3eV. At the same time, the Zn LMM Auger spectrum ( Figure 2 b) A peak different from that of metallic Zn (992eV) appears at about 989eV Auger electron kinetic energy, indicating that Zn is Zn 2+ Valence state. Comparison of ZnCr2O4 and ZnCr 1.2Fe 0.8 Cr 2p spectrum of O4 ( Figure 2 c) It can be seen that there is no significant difference between the two, and Cr 2p appears at 578.8 and 576.5 eV binding energies. 3 / 2 peaks, Cr 2p at 588.3 and 586.2 eV binding energies 1 / 2 Peak, indicating that the valence state of Cr is Cr 3+ .ZnCr 1.2 Fe 0.8 The Fe2p spectra of O4 and ZnFe2O4 are similar ( Figure 2 d), Fe2p appears at the binding energies of 711.0 and 713.5 eV 3 / 2 peak, while at Fe2p 3 / 2 The typical Fe 3+ Satellite peaks indicate that the valence state of Fe is Fe 3+ .
[0035] The ZnCr obtained in Example 1 1.2 Fe 0.8 O4 catalyst was characterized by transmission electron microscopy (TEM) Figure 3 ), it can be seen that the catalyst particle size distribution is in a narrow range, with an average particle size of about 6.6nm. The selected area electron diffraction (SAED) spectrum shows obvious diffraction rings of (311), (400), (422) and (440) crystal planes, indicating that the catalyst is a polycrystalline structure. High-resolution transmission electron microscopy (HRTEM) characterization revealed that the grains have regularly arranged lattice fringes with spacing of 0.252nm and 0.209nm, which belong to the (311) and (400) crystal planes, respectively, which is consistent with the XRD results.
[0036] Example 2
[0037] The ZnCr2O4 and ZnCr 1.2 Fe 0.8 The nitrogen temperature programmed desorption (N2-TPD) test was carried out on the O4 and ZnFe2O4 catalysts to determine the chemical adsorption performance of the prepared catalysts for nitrogen. The results are shown in Figure 4 and Table 1. Chemical adsorption is conducive to lengthening the nitrogen N≡N bond and activating it, but for nitrogen reduction to produce ammonia, the nitrogen adsorption strength is required to be moderate, neither too strong nor too weak. Figure 4 It can be seen that before the introduction of Fe, ZnCr2O4 showed nitrogen desorption peaks at 209.3 and 436.7 °C; similarly, ZnFe2O4 showed obvious desorption peaks at 220.7 °C and 371.9 °C, indicating that both had strong chemical adsorption of nitrogen. 1.2 Fe 0.8The nitrogen desorption peak temperature of O4 decreased to 184.5℃, indicating that the introduction of Fe reduced the chemical adsorption intensity of nitrogen. It is worth noting that it can be seen from Table 1 that ZnCr 1.2 Fe 0.8 The adsorption of nitrogen by O4 did not decrease significantly and remained at 0.950 cm 3 N2 / g cat, adsorption amount of ZnCr2O4 at 209.3℃ (0.945cm 3 N2 / gcat.) are almost equal, indicating that the introduction of Fe improves the adsorption performance of the catalyst for nitrogen and solves the problem of excessive nitrogen adsorption by pure Cr-based spinel catalysts.
[0038] Table 1 N2-TPD peak temperature and desorbed N2 volume
[0039]
[0040] Example 3
[0041] The ZnCr prepared in Example 1 2-x Fe x O4 (x = 0, 0.4, 0.8, 1.2, 1.6, 2) was used to test the electrochemical synthesis of ammonia. The prepared electrocatalyst was loaded on carbon felt as the cathode, 0.1 mol / L KOH aqueous solution was used as the electrolyte, and carbon felt was used as the anode. Nitrogen was blown to the cathode at a flow rate of 200 ml / min, and then the power was turned on. Constant voltage electrolysis was performed at a voltage of 2.1 V, and the ammonia produced by electrolysis was analyzed and determined. The results are shown in Figure 5 It can be seen that ZnCr 1.2 Fe 0.8 The ammonia production rate and Faradaic efficiency of O4 (x = 0.8) were as high as 29.26 μg h -1 cm -2 and 8.16%, which are significantly higher than those of ZnCr2O4 (x=0). The main reason is that the introduction of Fe improves the chemical adsorption and activation performance of the catalyst for nitrogen. At the same time, the ammonia production rate and Faraday efficiency of ZnFe2O4 (x=2.0) are the lowest, indicating that more HER side reactions may occur under the action of this catalyst.
[0042] Example 4
[0043] The difference from Example 1 is that the voltage is different. This example examines the performance of electrochemical ammonia synthesis under different electrolysis voltages. Figure 6 , Figure 6 ZnCr 1.2 Fe 0.8 The current density curve of O4 at different electrolysis voltages. It can be seen from the figure that as the electrolysis proceeds, the electrolysis current density remains stable within the electrolysis time, indicating that a smooth electrochemical reaction occurs on the catalyst. Figure 7 ZnCr 1.2 Fe 0.8 The performance results of O4 electrocatalytic ammonia production show that when the voltage is 1.5V, 10.08μgh -1 cm -2 The ammonia production rate and the Faradaic efficiency of up to 18.41% were achieved. With the increase of voltage, the electrolysis current increased almost linearly, and the ammonia production rate also increased synchronously. The maximum ammonia production rate of 29.26 μg h was obtained at 2.1 V. -1 cm -2 , at this time the Faraday efficiency is 8.16%.
[0044] Example 5
[0045] This embodiment is similar to embodiment 1, except that: in step (1), only corresponding amounts of zinc acetate, chromium chloride and ferric chloride are weighed in a ratio of 1:1.2:0.8, the hydrothermal temperature is 150°C, and the remaining steps are the same as embodiment 1 to prepare ZnCr 1.2 Fe 0.8 When O4 was electrolyzed at a constant voltage of 2.1 V, the ammonia production rate was 28.43 μg h -1 cm -2 , the Faraday efficiency is 8.09%.
[0046] Comparative Example 1
[0047] In order to compare with the catalyst prepared in Example 1 (ZnCr 1.6 Fe 0.4 O4) compared with Cr, Co is used to replace Cr, according to the chemical formula ZnCo 1.6 Fe 0.4 O4 gives a ratio of 1:1.6:0.4. Weigh 5mmol of zinc acetate and the corresponding amount of cobalt chloride and ferric chloride and dissolve them in deionized water. The remaining steps are the same as in Example 1. Use 3.0mol / L sodium hydroxide aqueous solution to adjust the pH of the solution to 10-12, add water to make the total volume of the solution 50ml, and then transfer it to a hydrothermal reactor with a polytetrafluoroethylene lining for hydrothermal reaction at 180°C for 8 hours. After the reaction, centrifuge to remove the supernatant to obtain a catalyst precursor, wash it with deionized water 3 times, and vacuum dry it. Roast it at 400°C in a muffle furnace for 1 hour, cool it naturally to room temperature, and grind it to obtain the desired electrocatalyst.
[0048] The sample obtained in Comparative Example 1 was subjected to XRD analysis. Figure 8 It can be seen that the XRD spectrum of the prepared sample is similar to that of ZnCr in Example 1. 1.6 Fe 0.4 XRD spectrum of O4 (see Figure 1The X-ray diffraction patterns of the samples prepared in Comparative Example 1 are obviously different from those of the samples prepared in Comparative Example 1 (x = 0.4), with obvious diffraction peaks appearing at 2θ = 31.8°, 34.4°, 36.3°, 47.6°, 56.6°, 62.9° and 67.9°, which are attributed to ZnO (standard card PDF no. 36-1451). The obvious characteristic diffraction peaks appearing at 2θ = 18.9°, 31.2°, 36.8°, 44.7°, 59.3°, 65.1° and 63.1°, which are attributed to ZnCo2O4 spinel (standard card PDF no. 23-1390), indicate that the sample prepared in Comparative Example 1 contains ZnO and ZnCo2O4 phases. It should be noted that although according to the chemical formula ZnCo 1.6 Fe 0.4 O4 gives a metering ratio of 1:1.6:0.4 to add various raw salts, but Figure 8 The XRD spectrum shown in the figure has no other peaks except the diffraction peaks that match those of ZnO and ZnCo2O4, especially no series of characteristic diffraction peaks that match those of ZnFe2O4 spinel (PDF no.22–1012), indicating that the sample prepared in Comparative Example 1 does not contain ZnFe2O4 spinel phase, and the ferric chloride added to the raw material does not generate any relevant iron-containing crystalline species (no extra peaks) after the synthesis reaction, or only generates amorphous non-crystalline Fe-based substances. Therefore, the crystal structure of the sample prepared in Comparative Example 1 is not pure ZnCo 1.6 Fe 0.4 O4 spinel, but a mixture of ZnO and ZnCo2O4 spinel.
[0049] When the sample obtained in Comparative Example 1 was electrolyzed at a constant voltage of 2.1 V, the ammonia production rate was 6.38 μg h -1 cm -2 , much lower than that of ZnCr prepared in Example 1 1.6 Fe 0.4 O4 catalyst (20.83 μg h -1 cm -2 ); the Faraday efficiency is 4.91%, which is also lower than that of ZnCr prepared in Example 1 1.6 Fe 0.4 O4 catalyst (5.07%).
[0050] Comparative Example 2
[0051] In order to compare with the catalyst (ZnCr 1.6 Fe 0.4 O4) compared with Fe, Co is used to replace Fe, according to the chemical formula ZnCr 1.6 Co 0.4O4 gives a ratio of 1:1.6:0.4. Weigh 5 mmol of zinc acetate and corresponding amounts of chromium chloride and cobalt chloride and dissolve them in deionized water. The remaining steps are the same as in Example 1.
[0052] Fig. 9 The XRD spectrum of the sample prepared in Comparative Example 2 is Fig. 9 It can be seen that the XRD spectrum of the prepared sample is similar to that of ZnCr in Example 1. 1.6 Fe 0.4 XRD spectrum of O4 (see Figure 1 Similar to the sample prepared in Comparative Example 2 (x = 0.4), obvious characteristic diffraction peaks appear near 2θ = 18.4°, 30.3°, 35.7°, 43.4°, 57.4° and 63.1°, which are attributed to ZnCr2O4 spinel (standard card PDF no. 22–1107) and ZnCo2O4 spinel (standard card PDF no. 23–1390), and no other miscellaneous peaks appear, indicating that the sample prepared in Comparative Example 2 has ZnCr 1.6 Co 0.4 O4 spinel structure, and no impurities. When electrolyzed at 2.1V constant voltage, the ammonia production rate is 14.34μg h -1 cm -2 , the Faraday efficiency is 4.26%, which is lower than that of ZnCr prepared in Example 1. 1.6 Fe 0.4 O4 catalyst.
[0053] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing zinc chromite spinel electrocatalyst, characterized in that: The specific steps are: The first step is to weigh zincate, chromate and ferrite in a certain proportion and dissolve them in a solvent, then add alkaline solution to adjust the pH to 10. ~ 12, then hydrothermally reacting and post-treating to obtain a dry catalyst precursor; The molar ratio of zincate, chromate and ferrite is 1:(2-x):x, where x is greater than 0 and less than 2; The hydrothermal synthesis temperature ranges from 150°C to 200°C; In the second step, the catalyst precursor obtained after drying in the first step is calcined in a muffle furnace, cooled naturally to room temperature, and then ground to obtain the desired electrocatalyst; In the first step, the hydrothermal synthesis time ranged from 4 hours ~ During the 12 hours, the vacuum drying temperature ranges from 60°C to 80°C; In the first step, the zincate includes zinc chloride, zinc sulfate, zinc nitrate and zinc acetate; the chromate includes chromium chloride, chromium sulfate and chromium nitrate; the ferrite includes ferric chloride, ferric sulfate and ferric nitrate; and the concentration of the zincate is 0.05-0.2 mol / L; In the second step, the calcination temperature ranges from 300°C to 500°C, and the calcination time ranges from 0.5 hours to 3 hours; The zinc chromite spinel has the general formula ZnCr 2-x Fe x O4 represents, 2-x, x represents the atomic ratio of each element, and x is greater than 0 and less than 2.
2. The method according to claim 1, characterized in that: In the first step, the solvent is deionized water; and the alkaline solution is a 3.0-6.0 mol / L sodium hydroxide or potassium hydroxide aqueous solution.
3. The method according to claim 1, characterized in that: In the first step, the hydrothermal reaction and post-treatment are to transfer the metal precursor into a hydrothermal reactor with a polytetrafluoroethylene lining for hydrothermal reaction at a certain temperature for a certain time. After the reaction, the supernatant is removed by centrifugation to obtain a catalyst precursor, which is washed three times with deionized water and vacuum dried.
4. The method according to claim 1, characterized in that: In the first step, the zincate, chromate and ferrite are zinc acetate, chromium chloride and ferric chloride respectively, the molar ratio of the three is 1:1.2:0.8, the concentration of zinc acetate is 0.1 mol / L, the hydrothermal synthesis temperature is 180°C, and the hydrothermal synthesis time is 8 hours; in the second step, the roasting temperature is 400°C, and the roasting time is 1 hour.
5. Claim 1 ~ 4. A zinc chromite spinel electrocatalyst obtained by the method described in any one of claims 4.
6. The zinc ferrochromate spinel electrocatalyst according to claim 5, characterized in that: x is selected from any number among 0.4, 0.8, 1.2, and 1.
6.
7. According to claim 1 ~ 4. The electrocatalyst prepared by the method described in any one of the preceding claims is used in electrochemical synthesis of ammonia, characterized in that The specific process is: the prepared electrocatalyst is loaded onto the carbon felt as the cathode, the carbon felt without the catalyst loaded is used as the anode, the KOH aqueous solution is used as the electrolyte, high-purity nitrogen is blown to the cathode at a certain flow rate, and then a DC power supply is connected for electrolysis.
Citation Information
Patent Citations
Hydrothermal preparation method for spinel type ferrite nanopowder
CN102649639A
Cobalt oxide of spinel structure and preparation method and application thereof
CN110316768A